A New Way for Preparation and Characterization of Cr-Doped LiMnO2 Cathode Materials for Lithium Ion Batteries. Issue 6 (2nd June 2016) - Li, Yi; Zhou, Zhiyang; Jicail, Liang; Ye, Kaiqi; Yu, Kaifeng
Abstract : o-LiMnO2 and LiMn1−x Crx O2 (x = 0.1) powders were synthesized via hydrothermal method after being calcined. Crystalline structure, surface morphology, and electrochemical properties of the prepared powders are investigated by XRD, SEM, and cyclic voltammetric studies. From the results, it was found that LiMnO2 cathode with a small amount of doping Cr is mostly orthorhombic forms. It could not only affect the structure of the specimens, but also improve cycling performance and reversible capacity and it could reach 190 mAh/g after 50 cycles.